A large-scale study integrating CEA and tumor deposits to evaluate prognosis in colon cancer patients - Fan, Ya’nan; Sun, Yun; Hu, Xiaojie; Zhang, Lifei; Dong, Jiantao; Liu, Fei; Wang, Zhiqiang; Cai, Jianhui (Frontiers in Oncology, 2025)
BackgroundReliable prediction of long-term survival in colon cancer remains limited by staging system constraints. CEA and tumor deposits (TD) are known prognostic markers, but their combined predictive value is underexplored.Materials and MethodsWe retrospectively analyzed 1, 029 patients with locally advanced colon cancer who underwent radical resection. A CEA-TD scoring system was developed and integrated with key clinicopathologic variables to construct a prognostic nomogram.ResultsBoth TD(+) and elevated CEA levels were independently associated with significantly worse overall survival (HR for TD = 1.985, CEA = 2.209; all P < 0.01). The CEA-TD score effectively stratified patients into four risk categories, each with distinct survival outcomes (P < 0.001). The final nomogram, incorporating CEA-TD score, T stage, N stage, grade, and tumor location, demonstrated high predictive performance, with AUCs of 0.796, 0.834, and 0.807 for 1-, 3-, and 5-year OS in the training cohort, and comparable values in internal and external validations. The C-index reached 0.800, outperforming traditional prognostic factors. Kaplan-Meier and risk curve analyses confirmed the model’s discriminative capacity.ConclusionsThe CEA-TD-based nomogram offers accurate, clinically applicable risk stratification for LOCC patients, supporting personalized treatment strategies and improved prognostic assessment.